2016
DOI: 10.1097/igc.0000000000000772
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Standardized Uptake Value of Pelvic Lymph Nodes in [18F]-Fluorodeoxyglucose Positron Emission Tomography Is a Prognostic Factor for Para-Aortic Lymph Node Recurrence in Pelvic Node-Positive Cervical Cancer Treated With Definitive Chemoradiotherapy

Abstract: SUVPLN is a statistically significant prognostic factor of PALN recurrence and survival after definitive CCRT for pelvic node-positive SCC of the uterine cervix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Of these, 348 publications unrelated to the study were excluded by carefully reading the title and abstract, and the remaining 39 publications were further examined by screening the full text. Finally, 17 publications were studied, including 4 that simultaneously analyzed overall survival (OS) and progression-free survival (PFS) as prognostic indicators, 4 that analyzed OS and disease-free survival (DFS) as prognostic indicators, 5 studied with DFS alone, 3 articles with the most endpoints of OS alone, and 1 studied with PFS alone (Figure 1) [622]. The publication period of the literature was between 2003 and 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 348 publications unrelated to the study were excluded by carefully reading the title and abstract, and the remaining 39 publications were further examined by screening the full text. Finally, 17 publications were studied, including 4 that simultaneously analyzed overall survival (OS) and progression-free survival (PFS) as prognostic indicators, 4 that analyzed OS and disease-free survival (DFS) as prognostic indicators, 5 studied with DFS alone, 3 articles with the most endpoints of OS alone, and 1 studied with PFS alone (Figure 1) [622]. The publication period of the literature was between 2003 and 2017.…”
Section: Resultsmentioning
confidence: 99%
“…Para-aortic nodal control can be addressed through pre-therapeutic laparoscopic para-aortic lymph node dissection or by increasing the use of para-aortic irradiation in selected patients with nodal involvement at diagnosis who are at higher risk of para-aortic and distant relapse. The number of nodes (≥3), location (common iliac), PET avidity [69] , [70] , [71] , and to a lesser extent size of nodes [72] , may be predictors of para-aortic and systemic failure. Systematic prophylactic para-aortic irradiation in node-positive patients has been shown to produce high levels of nodal control in mono-institutional reports [73] .…”
Section: The Embrace II Study – Rationale For Change Of Practicementioning
confidence: 99%
“…Regarding the prognostic value of the size of lymph node metastasis measured by imaging modalities, Wang et al have reported that in patients treated with de nitive radiotherapy, the presence of three or more lymph nodes ≥ 1 cm in short axis diameter measured by CT or MRI was an independent prognostic factor for overall survival 17 21 . This nding suggests that 18 F-FDG PET might be also a prognostic biomarker in cervical cancer, although no previous study has compared its utility as a prognostic biomarker between size measured by imaging modalities and uptake of 18 F-FDG PET.…”
Section: Discussionmentioning
confidence: 99%